Mengintegrasikan Kembali Standar Pendidikan Paripurna yang Dicontohkan oleh Nabi Muhammad SAW ke dalam Standar Pendidikan abad 21 - Kajin, Sudar (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2020)
This paper aims to describe: 1) The way the Prophet Muhammad taught the Qur'an to his students which can be adopted into 21st century educational standards; 2) Elements of the ideal standard of Islamic education more than a thousand years ago and its influence is still felt today. This research is a qualitative literature study to provide a set of insights on how phenomenons are interpreted in the literature. Research design becomes a reflexive process at each stage of the research. Qualitative analysis involves two activities: 1) developing an awareness of the types of data that can be examined and how they can be explained. From the results of the discussion, it can be concluded as follows: 1) the way the Prophet Muhammad taught the Qur'an (certainly supported by hadith) is the past, present and future form: as language is to be read (in terms of linguistics with various attributes), as past history ( to be learned as a lesson today), as science and technology to be analyzed (in terms of methodology and attributes), as nubuwwah (aspects of scientific predictions that have not been discovered, to life in the hereafter). 2) The ideal standard of Islamic education is more than a thousand years ago and its influence is still felt today, at least it contains elements of the personal teacher, namely the Prophet Muhammad SAW himself including: No students are left behind in their class, perfect and consistent speakers so that they are easily understood by students, Life with an example that makes students have no trouble imitating him and patience through adversity.